Product and regional profile of postindustrial economy services in the economy of Kazakhstan - Pritvorova, T.P.; Abzalbek , E.Zh. (BUKETOV BUSINESS REVIEW, 2019)
The article deals with the postindustrial service sector in the economy of Kazakhstan, conditions and dynamics of which is a characteristic feature of modern techno-technological mode in the developed countries of the world. Information and communication, business and professional services are included into the sector. The authors explore the regional profile of postindustrial services in Kazakhstan and identify the level of these activities centralization in the regions of Kazakhstan. Using the method of rating evaluation and the method of absolute differences for grouping of regions in terms of production of postindustrial services, the authors give qualitative characteristic of designated groups. Referring to the product profile of activity in the framework of post-industrial services, authors make an in-depth analysis of all types of services within three aggregated positions: computer programming services; information services; services in the field of architecture, engineering survey, technical testing and analysis. Characteristics of the dynamics and structure of these services supply on the market, concentration of services in the regions of Kazakhstan are evaluated. Services, which are characterized by the absolute and relative increase in all regions of the country are highlighted, which makes it possible to draw conclusions about the vector of Kazakhstani economy development. The main positive trend is that the specific weight and growth rate of engineering services are on the first place, which generally complies with the trend of transition to a post-industrial economy, with its emphasis on high-tech servicers for all sectors.